2007
DOI: 10.1111/j.1432-2277.2006.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

12-month safety and efficacy of everolimus with reduced exposure cyclosporine in de novo renal transplant recipients

Abstract: Summary The proliferation signal inhibitor everolimus (Certican), has demonstrated efficacy with full‐dose cyclosporine (CsA) (Neoral®). Two multicenter randomized controlled studies were performed to compare 12‐month efficacy and safety of everolimus 1.5 and 3.0 mg/day with reduced‐dose CsA. Study 1 enrolled 237 de novo renal allograft recipients, randomizing 222 nonblack patients to either everolimus 1.5 or 3.0 mg/day, with the Neoral® dose guided by C2 (monitoring of CsA concentration 2 h after dosing). Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 21 publications
2
53
0
6
Order By: Relevance
“…361 The model, however, applied costs to the TAC arm at a quoted BNF recommended dose of 0.25 mg/kg/day for a group of individuals of 70 kg mean weight, thus resulting in a mean daily dose of 17.5 mg, which is considerably higher than the actual drug use that corresponds to the efficacy outcomes used by the model. The dose behind the TAC drug acquisition costs used in the Novartis submission is also larger than the mean daily doses for immediate-release TAC reported by Tedesco-Silva et al, 349 which Astellas adopted in its submission, and which are consistent with the report of Dean et al…”
Section: Critical Appraisal Of Company Submissionssupporting
confidence: 76%
See 1 more Smart Citation
“…361 The model, however, applied costs to the TAC arm at a quoted BNF recommended dose of 0.25 mg/kg/day for a group of individuals of 70 kg mean weight, thus resulting in a mean daily dose of 17.5 mg, which is considerably higher than the actual drug use that corresponds to the efficacy outcomes used by the model. The dose behind the TAC drug acquisition costs used in the Novartis submission is also larger than the mean daily doses for immediate-release TAC reported by Tedesco-Silva et al, 349 which Astellas adopted in its submission, and which are consistent with the report of Dean et al…”
Section: Critical Appraisal Of Company Submissionssupporting
confidence: 76%
“…349 The company also cites the results of an indirect comparative analysis conducted by Bristol-Myers Squibb, which showed 'no significant difference' between BEL and TAC for mortality, graft loss or GFR at 12 and 36 months (All Wales Medicines Strategy Group 2012) 350 and higher ARR and lower incidence of NODAT for BEL than for TAC.…”
Section: Efficacy and Effectiveness Evidencementioning
confidence: 99%
“…, and is highly effective in preventing acute rejection in renaltransplant recipients (6)(7)(8)(9). Although, in initial trials, everolimus plus standard-exposure CsA (ST-CsA) demonstrated equivalent efficacy to MMF plus ST-CsA in de novo renal-transplant recipients, renal function was reduced in everolimus-treated patients (6,9,10).…”
Section: Everolimus Is a Mammalian Target Of Rapamycin (Mtor) Inhibitmentioning
confidence: 99%
“…37 Less data are available about everolimus, but in the A2306 and A2307 studies, conducted in de novo renal-transplant recipients, proteinuria (determined by a spot urine protein/creatinine ratio) was detected in 5% of patients. 38 The onset of abundant urinary protein excretion is of importance because proteinuria is a marker for the risk of progressive decline in renal function 39 and is an important predictor of renal dysfunction following conversion from a CNI-to a PSI-based regimen. 40 However, the mechanisms of PSI-induced proteinuria continues to be debated.…”
Section: Proteinuriamentioning
confidence: 99%